A relational approach to supervision’: Some reflections on supervision from an existential-phenomenological perspective - Plock, Simon du (2018)
This paper draws attention to the dearth of information on clinical supervision in the existential-phenomenological literature. It suggests that this should be of concern to existential trainers and practitioners since it seems indicative of a lack of the reflectiveness and clarity which are at the core of existential-phenomenological practice. The author proposes an experiential approach to this situation which utilizes some aspects of existential therapy to facilitate exploration of the concept of ‘supervision’ per se from an existential perspective. The author reminds us of the centrality of relationship in existential-phenomenological therapy, particularly in the form of healing encounter espoused by Buber and the equality of client and therapist engaged in an investigation of the difficulties in living which is proposed by Heidegger. In doing so, the author raises the possibility that an ‘attitude’ to, rather than a model for, existential-phenomenological supervision may emerge which takes relationship as its primary focus: he describes this as a ‘relational approach to supervision